Longitudinal Associations Between Energy Drink Consumption, Health, and Norm-Breaking Behavior Among Swedish Adolescents - Svensson, Åsa; Warne, Maria; Gillander Gådin, Katja (Frontiers in Public Health, 2021)
Objectives: To describe the intake of energy drinks (EDs) among a sample of Swedish adolescents while considering health-related variables, and to investigate the longitudinal associations between ED consumption, health, and norm-breaking behavior. Longitudinal studies on this topic are scarce. Methods: Questionnaire data were collected in the northern part of Sweden in 2010–2011 from 1,622 adolescents in grades 6–9. Analyses were performed using a chi-squared test and logistic regression. Results: Seventy-four percent of the boys and 54% of the girls had consumed EDs (P < 0.001). ED consumption was associated with variables related to low health, low support levels, and norm-breaking behavior. The associations were generally stronger among the girls and the boys who consumed EDs at least once a week. ED consumption was a predictor of worse health and norm-breaking behavior 1 year later. Adjusted odds ratios ranged from 1.53 (95% CI: 1.07, 2.20; school-related stress) to 4.88 (95% CI: 2.28, 10.43; gaming-related truancy). Conclusions: Health promotion activities benefit from a broad approach but could focus on girls who consume EDs and those boys with the highest consumption levels.